Effects of herbicides on growth and number of actinomycetes in soil and in vitro - Šantrić, Ljiljana R; Radivojević, Ljiljana; Gajić Umiljendić, Jelena; Sarić-Krsmanović, Marija; Đurović-Pejčev, Rada (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
This study was conducted under laboratory conditions to investigate the effects of herbicides (nicosulfuron, metribuzin and glyphosate) on the number of actinomycetes in soil and growth of several isolates of actinomycetes in vitro. The lowest tested concentrations equalled the recommended rates (1X), while the other three were five-fold (5X), ten-fold (10X) and fifty-fold (50X). Samples were collected for analysis 3, 7, 14, 30 and 45 days after herbicide application. Treatment with the two highest concentrations of herbicides (10X and 50X) caused a significant inhibition of the number of actinomycetes in soil and growth of the isolates in vitro. The obtained data indicated that the effect depended on the type of herbicide, application rate, duration of activity and actinomycetes isolate. The study suggests that herbicide applications in soil caused transient effects on the growth and development on actinomycetes community in soil.
Keywords: Herbicides; Actinomycetes; Soil